2007
DOI: 10.1530/rep-07-0079
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of porcine oocytes during in vitro maturation reveals essential role for the ubiquitin C-terminal hydrolase-L1

Abstract: In this study, we performed proteomic analysis of porcine oocytes during in vitro maturation. Comparison of oocytes at the initial and final stages of meiotic division characterized candidate proteins that were differentially synthesized during in vitro maturation. While the biosynthesis of many of these proteins was significantly decreased, we found four proteins with increased biosynthetic rate, which are supposed to play an essential role in meiosis. Among them, the ubiquitin C-terminal hydrolase-L1 (UCH-L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 38 publications
2
38
1
Order By: Relevance
“…The deubiquitinating enzymes (DUBs) have been implicated, for example, in cell growth, differentiation, oncogenesis, and development and in regulation of chromosome structure [6]. One such DUB, ubiquitin C-terminal hydrolase-L1 (UCHL1), is highly abundant in mammalian oocytes [7]. It is also expressed in neurons and in the testis [8,9]; however, abnormal expression of UCHL1 is also found in many primary lung tumors [10,11] and in colorectal cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…The deubiquitinating enzymes (DUBs) have been implicated, for example, in cell growth, differentiation, oncogenesis, and development and in regulation of chromosome structure [6]. One such DUB, ubiquitin C-terminal hydrolase-L1 (UCHL1), is highly abundant in mammalian oocytes [7]. It is also expressed in neurons and in the testis [8,9]; however, abnormal expression of UCHL1 is also found in many primary lung tumors [10,11] and in colorectal cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…UCHL1 is essential for maintaining the ubiquitin-proteasome system and is abundantly expressed in mouse ova (Sekiguchi et al 2006). Similarly, previous studies have identified UCHL1 as a maternal protein necessary for oocyte maturation (Ellederova et al 2004, Massicotte et al 2006, Susor et al 2007). Thus, a logical potential conclusion would be that the NLRP5 protein level is potentially regulated by the ubiquitin-proteasome system for oocyte maturation.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, ubiquitin mRNA levels are upregulated when the NLRP5 protein decreases during oogenesis and embryogenesis (Robert et al 2002, Pennetier et al 2006, Ohsugi et al 2008. Furthermore, a UCHL1 inhibitor prevents germinal vesicle (GV) breakdown and the metaphase I-anaphase transition in porcine oocytes by downregulating the ubiquitin-proteasome system (Susor et al 2007). Thus, excess NLRP5 protein resulting from downregulating the ubiquitin-proteasome system prevents complete oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin C-terminal hydrolase L1 (UCHL1), a UPP enzyme with hydrolase and ligase activity, is one of the most abundant proteins in porcine oocytes (Susor et al 2007). The modulation of UCHL1 activity leads to polyspermy during porcine and mouse IVF, suggesting that UCHL1 is involved in the regulation of sperm incorporation and/or events leading to the establishment of the ZP or oolemma block to polyspermy (Sekiguchi et al 2006;Yi et al 2007).…”
Section: Upp and Anti-polyspermy Defensementioning
confidence: 99%